Integrated Model for Supervision Handbook For Mental Health and Psychosocial Support - IFRC Reference Centre for Psychosocial Support; Trinity Centre for Global Health, Trinity College Dublin (My University, 2023)
The IMS is the product of extensive engagement and consultation. Throughout its development, participatory methods were used to consult on all aspects of its content to reflect the voices of the broadest range of MHPSS actors across sectors. An advisory group comprised of leading global experts on MHPSS in emergency settings actively guided all stages of the development of the IMS. The advisory group provided invaluable feedback and reflection throughout the whole process. Developing the Integrated Model for Supervision (IMS) A desk review of literature on MHPSS and protection supervision provided a rapid assessment of key evidence to inform initial project planning and development. Key informant interviews were then conducted with MHPSS actors from all professional levels and backgrounds. This included supervisors, supervisees, organisational leadership, and donors, based in organisation headquarters and in the field around the world. These interviews provided rich information about current practice and insights for future directions. This formed the basis for the early draft of the IMS.